2007
DOI: 10.1097/01.bpb.0000271327.79481.e3
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Gait Velocity and Mean Knee Flexion in Stance of Ambulatory Children With Spastic Diplegia Four Years or More After Multilevel Surgery

Abstract: Factors associated with longer-term outcomes of multilevel orthopaedic surgery in ambulatory children with cerebral palsy using a multivariate approach were evaluated using a retrospective pretest-posttest design. The population included 20 ambulatory children with spastic diplegia who had undergone multilevel orthopaedic surgery with a minimum of 4-year interval between a preoperative and a postoperative gait assessment. Multiple regression analysis was used to identify factors associated with postoperative v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…A large percentage of subjects seen in clinical motion laboratories have a diagnosis of cerebral palsy (CP). Several research studies have examined outcomes following surgical intervention using a variety of different standardized tests and quantitative measures [14][15][16][17][18][19]. Gates et al [20] investigated the functional changes between children with spastic diplegia undergoing surgery versus those with non-surgical treatment.…”
Section: Introductionmentioning
confidence: 99%
“…A large percentage of subjects seen in clinical motion laboratories have a diagnosis of cerebral palsy (CP). Several research studies have examined outcomes following surgical intervention using a variety of different standardized tests and quantitative measures [14][15][16][17][18][19]. Gates et al [20] investigated the functional changes between children with spastic diplegia undergoing surgery versus those with non-surgical treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Analysis of individual gait parameters, such as gait velocity or mean knee flexion in stance would likely reveal different results [7,24]. As overall walking abilities were of interest, using GGI is an appropriate outcome measure.…”
Section: Discussionmentioning
confidence: 99%
“…In the longer term (more than 3 years follow up) however, it can be difficult to predict who will benefit the most from surgical intervention and few studies have attempted to look beyond 3 years. Adolfsen et al [6] and Gannotti et al [7] identified children with crouch who have maintained surgical gains at the knee 4 years post-operatively. There is little evidence to support continued or maintained improvement of function into adulthood [8].…”
Section: Introductionmentioning
confidence: 98%
“…These studies are typically small, retrospective, uncontrolled case series looking at preintervention and postintervention comparisons that demonstrate some improvements in the short term in outcomes limited to the level of body structures and body functions, such as range of motion, spatiotemporal gait parameters, and kinematic or kinetic improvements on gait analysis. 18,59,[79][80][81] The clinical signifi cance of these fi ndings is less clear, with only a few case series (Level IV evidence) reporting benefi ts in some functional outcomes at the level of activities and participation. [80][81][82][83][84] A few retrospective, case-control or cohort studies (Level III evidence) compare different surgical techniques, but few prospective clinical trials compare the effectiveness of these procedures.…”
Section: Evidence For Specifi C Orthopedic Procedures and Techniquesmentioning
confidence: 93%